2013
DOI: 10.7202/1014862ar
|View full text |Cite
|
Sign up to set email alerts
|

Moving From the Margins: Culturally safe teacher education in remote northwestern British Columbia

Abstract: In 2007 the University of Northern British Columbia initiated a two-year elementary teacher education program at the Northwest Campus in Terrace, British Columbia. The program was designed to meet specific community needs in the North that arise from inequities in the cultural safety of Indigenous teachers and students. The authors share three collegial inquiries into the program’s contribution toward improving cultural safety in K-12 schools and meeting social justice challenges in the region’s communities. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The findings of this study demonstrate cultural safety teacher training is a means towards MOE and PSE institutional goals of reconciliation with Indigenous peoples, but it is a start of a learning journey that will assist with reconciliation and not an end to itself. Training teachers to safely teach and integrate Indigenous content is not only a matter of adjusting the scope of education to reduce settler biases and harmful stereotypes, but also helps teachers to establish new connections and relations with Indigenous peoples that are respectful and empathic to the impacts of colonization (Dion, 2008;Harrison et al, 2012;Keliipio et al, 2018;Murray-Orr & Mitton-Kukner, 2017;Vetter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings of this study demonstrate cultural safety teacher training is a means towards MOE and PSE institutional goals of reconciliation with Indigenous peoples, but it is a start of a learning journey that will assist with reconciliation and not an end to itself. Training teachers to safely teach and integrate Indigenous content is not only a matter of adjusting the scope of education to reduce settler biases and harmful stereotypes, but also helps teachers to establish new connections and relations with Indigenous peoples that are respectful and empathic to the impacts of colonization (Dion, 2008;Harrison et al, 2012;Keliipio et al, 2018;Murray-Orr & Mitton-Kukner, 2017;Vetter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Harrison et al's (2012) evaluation of the program, they found that as pre-service teachers look into the underlying ideologies, values, and worldviews of the curricula, students quickly recognize the lack of Indigenous knowledges across subject areas; a lack of diversity also known to exist in lesson plans and modes of assessment for K-12 students (Marom, 2019). Moreover, pre-service teachers are encouraged to consider the impacts this lack of diversity may have on cultural safety within education systems as well as the accessibility of the content for Indigenous students (Harrison et al, 2012). With this level of reflection, pre-service teachers will become aware of their implicit biases in the classroom, as well as see the potential of their role as future teachers to shift the focus of current curricula to incorporate Indigenous content and improve its accessibility for all students.…”
Section: Challenging Personal Belief Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly half of the studies targeted students of these disciplines (48%) (26,28, 29, 32, 34, 39, 42-44, 46, 49, 52, 57, 59, 64-68, 70, 71, 73-78, 81, 83-87, 89, 91, 92, 95, 98, 99, 101-104, 106-109, 112-114, 118, 121, 123, 124, 135, 137, 139, 140, 142, 144, 150, 152, 153, 160), while a slightly smaller proportion targeted professionals and/or academics (46%)(30, 31, 35-38, 40, 41, 45, 47, 50, 51, 53-56, 58, 60-63, 69, 72, 79, 80, 82, 88, 94, 96, 97, 100, 105, 110, 111, 115-117, 120, 122, 126-133, 136, 138, 141, 143, 145-149, 154- 159). Only one in twenty articles targeted both professionals/academics and students (6%)(33,48,90,93,119,125,134,151). In terms of the content within the articles selected for this review, just over half of the articles (51%) either articulated or cited a cultural safety (or similar) concept (e.g.…”
mentioning
confidence: 99%